COGNITIVE PSYCHOLOGY IN TEACHING FOREIGN LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In English teaching, cognitive psychology pays more attention to the driving role of concept and situational role of textbook, which is the further development of students’ intelligence for the purpose of improving students’ competence for language use. Based on this, the foreign language learning and teaching based on cognitive psychology is discussed in this paper.